Pengaruh Hedonic Consumption Tendency, Fashion Involvement, dan Visual Merchandising terhadap Impulsive Buying pada Gen Z di Oh Some Carefour Medan - Syahida, Tiara Nurul; Marliyah, Marliyah; Nurbaiti, Nurbaiti (Universitas Proklamasi 45, 2025)
This study aims to examine the influence of hedonic consumption tendency, fashion involvement, and visual merchandising on impulsive buying among Gen Z at Oh Some! Carefour Medan. The growing trend of unplanned purchases among Gen Z highlights the need to examine the emotional and visual factors that influence their purchasing behavior. A quantitative survey method was used, involving 96 respondents aged 18–24. The data were analyzed using multiple linear regression in SPSS. The results show that hedonic consumption tendency and fashion involvement have a positive and significant effect on impulsive buying, while visual merchandising shows no significant effect. Simultaneously, all three variables significantly influence impulsive buying, contributing 42.5%. These findings suggest that emotional aspects and fashion involvement play a key role in shaping impulsive buying behavior among Gen Z.